Maternal Secondhand Smoke Exposure Enhances Macrosomia Risk Among Pregnant Women Exposed to PM2.5: A New Interaction of Two Air Pollutants in a Nationwide Cohort - Luo, Yunyun; Zhang, Yuelun; Pan, Hui; Chen, Shi (Frontiers in Public Health, 2021)
BACKGROUND Fine particulate matter (PM2.5) is one of the most common outdoor air pollutants and secondhand smoking (SHS) is an important source of inhalable indoor air pollution. Previous studies were controversial and inconsistent about PM2.5 and SHS air pollutants on neonatal birthweight outcomes and no studies assessed the potential interactive effects between PM2.5 and SHS on birthweight outcomes. PURPOSE To investigate the interaction between gestational PM2.5 and SHS air pollution exposure on the risk of macrosomia among pregnant women, and examine the modifying effect of SHS exposure on the association of PM2.5 air pollution and birthweight outcomes during pregnancy. METHODS Research data were derived from the National Free Preconception Health Examination Project (NFPHEP), which lasted 3 years. At least 240,000 Chinese women from 220 counties were enrolled in this project. PM2.5 exposure concentration was obtained using a hindcast model specific for historical PM2.5 estimation from satellite-retrieved aerosol optic depth. Different interaction models about air pollution exposure on birthweight outcomes were established, according to different confounding factors adjustment and different pregnancy stages. The establishment of interaction models was based on multivariable logistic regression and main confounding factors were maternal age at delivery, and pre-pregnancy body mass index (BMI) of participants. SHS subgroups analysis was conducted to further confirm the results of interaction models. RESULTS 197,877 participants were included in our study. In full-adjusted interaction model, maternal exposure to PM2.5 was associated with an increased risk of macrosomia in whole, the first, second, and third trimester of pregnancy(p<0.001). The interactive effect was statistically significant between maternal exposure to PM2.5 and SHS on the risk of macrosomia in the whole (interaction p<0.050) and the first-trimester pregnancy (interaction p<0.050), not in the second (interaction p>0.050) or third trimester (interaction p>0.050) of pregnancy. The higher frequency of SHS exposure prompted stronger interaction between the two air pollutants in the whole pregnancy and the first-trimester pregnancy. CONCLUSIONS In the whole and first-trimester pregnancy, maternal exposure to SHS during pregnancy enhanced the risk of macrosomia among pregnant women exposed to PM2.5 air pollutants, and the interaction became stronger with the higher frequency of SHS exposure.